TO THE STUDY OF THE HERPETOBIUM OF MENDYKARA DISTRICT OF KOSTANAY REGION - Rulyova, М.М.; Bobrenko, M.A.; Kabdullina, D.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2020)
In the work described here the results of a study of herpetobium in four model sites (virgin land, young fallow, old-growth fallow, wheat field) located in the Mendykara district of Kostanay region are presented. The article includes information on the taxonomic composition of herpetobium, dynamic density. The data of a comparative analysis of herpetobium for 2010 and 2019 on virgin and old-age fallow are given.
Keywords: herpetobium; pests; Kostanay region; coleoptera; virgin land; fallow; agrocenosis